中部日本,高野層ボーリングコアの全有機炭素含有率変動に基づく更新世後期の古気候変動の高解像度復元 - Tawara, T; Kumon, F; Nagahashi, Y; Kakuta, N; Nozue, Y (Journal of the Sedimentological Society of Japan)
The Takano Formation of late Pleistocene lacustrine sediment is distributed at the southern Nagano City. The TKN-2004 core, 53.88 m long, was taken at the central part or the basin, and is composed mostly or homogenous clayey silt. Age of the sediment was estimated from the relationship between radiometric ages and calibrated depths of DKP,Aso-4,K-Tz,Ata and Aso-2tephras, postulating that the sedimentation rate is constant.Paleoclimate from 169ka to 37ka was reconstructed on the basis of TOC content variation. The long-term TOC fluctuations are concordant with the SPECMAP curve. This result is supported by pollen composition. The short-term variations are similar to stadial-interstadial cycles in the Greenland ice cores, and most of warm peaks can be correlated with IS 9 to 25. 長野市南部に分布する更新世後期の湖成層である高野層において,全層ボーリングを行い53.88mの連続したコア試料を得た.コア試料は,黒灰色ではぼ均質な粘土質シルト～シルトの層相を示し,多数のテフラ層を挟んでいる.これらのうち5つの広域指標テフラ(DKP,Aso-4,K-Tz, Ata,Aso-2)の放射年代値と補正深度を用いて年代モデルを作成した.高野層のTOC含有率の経年変動は,本コア試料中の花粉組成変化と同調しており,およそ169ka～37kaにおける数万年周期の長期の気候変動を示している.この変動はMIS 6-3前半における海洋酸素同位体比変動と同調しており,各ステージに対比される長期の温暖期･寒冷期が認識できた.また,数百～数千年周期の短期の寒暖変動も存在しており,これらは亜氷期-亜間氷期サイクルに相当すると考えられる.また,それらの温暖期の多くはIS9～25に対比される可能性がある. Article Journal of the Sedimentological Society of Japan. 64:37-41 (2007) journal article